Prurience, punishment and the image: Reading 'law-and-order pornography'. (May 2017) - Dymock, Alex
This article aims to expand interpretations of the representational and spectatorial politics of images by investigating what Wacquant has termed 'law-and-order pornographies'. By this, he refers to images of crime and punishment accorded signifiers of the pornographic and the prurient in order to describe the fusion of the erotic and the punitive. The first part of the article brings into conversation the fields of porn studies and visual criminology. It examines more closely what is at stake in imbuing crime images with the grammar of the pornographic. The second part of the article argues that the application of the pornographic to images of law and order has been refracted back onto the sphere of adult entertainment, in particular, the phenomenon of 'revenge pornography'.